A sensitive and reliable RP-HPLC method for the detection of cimetidine - a H2 receptor antagonist in human plasma - Helal Uddin, A.B.M.; Azad, Abul Kalam; Mia, Abdur Rashid; Othman, Liyana Zafirah (AMG Transcend Association, 2019)
Bioanalytical methods for bioequivalence studies require high sensibility and rapidity due to the large number of samples and the low plasma concentration of drugs. The present study aimed to develop and validate a high-performance liquid chromatography method to quantify cimetidine (CMT) in human plasma and to apply it in a bioequivalence study. Spiked plasma of 500 µl (l, m and h concentration) was used for the assay. The HPLC injection volume was 20μl of the reconstitute sample where, 2 ml of ethyl acetate used for extraction purposes. Cimetidine was prepared separately for low (80 ng/ml), medium (2000 ng/ml) and high (3600 ng/ml) concentrations and internal standard (ranitidine) concentration was 3000 ng/ml. Freeze thawing and long terms stability were conducted at -25º c. The individual calibration curve for spiked standards was linear with R2= 0.99. The inaccuracy values for QC samples were within 15% of the actual value and not more than 20% for the LOQ. The limit of quantitation (LOQ) was 40 ng/ml, which was also the lowest concentration of cimetidine that was quantitated with the variability of 5.9%. The within day precision and between day precision for LOQ were 10.8 and 5.9 respectively. The retention time for the analyte was 4.1-4.5 minutes during the within a day and between day results. The mean % inaccuracy values for low, medium and high concentration were 6.8, 5.6 and 7.8 respectively for within day and 2.4, 6.1 and 7.9 respectively for between days. The within day and between day % inaccuracy for LOQ concentration was 12.4 and 5.5 respectively. The mean recoveries for low, medium and high concentration of cimetidine were 80.2, 70.9 and 74.2. The overall mean recovery for cimetidine was 75.1%. The maximum inaccuracy for freeze thaw cycle and long term stability samples for low, medium and high was found with CV less than 15% for all concentrations, indicating that cimetidine is stable. The developed method was precise and accurate and was suitable to be applied for the bioequivalence study of cimetidine.